Bias Gender Pendidikan Islam Indonesia : Gender Bias In Indonesian Islamic Education - HM. Syamsudini (An-Nisa’ Journal of Gender Studies, 2015)
In the context of Indonesian Muslim society, male dominance is still so strong that contextualizing the spirit of non-discrimination in Islam becomes inappropriate when confronted with reality. The majority of Muslim communities generally believe that it is best to keep men and women in separate spaces, and that the intrusion of women into male domains will cause “chaos” that will destroy the basic order in all matters. The difficulty of access for women to obtain education is undeniably a legacy of Islamic religious traditions that were influenced by patriarchal bias when fiqh law was codified. Although the tradition itself is not always supported by the Qur'an, it has been and will continue to be influential in determining the opportunities available to women. Thus, the fact that education for women is minimal has become a common phenomenon in the Islamic world. Dalam konteks masyarakat muslim Indonesia dominasi laki-laki masih demikian kuat, sehingga kontekstualisasi semangat nondiskriminasi dalam Islam menjadi tidak sesuai ketika dihadapkan dengan realitas. Mayoritas masyarakat muslim pada umumnya percaya bahwa paling baik menjaga laki-laki dan perempuan dalam ruang yang ditetapkan terpisah, dan bahwa penerobosan perempuan ke dalam wilayah laki-laki akan menyebabkan "kekacauan" sehingga akan merusak tatanan dasar dalam segala hal. Sulitnya akses bagi perempuan untuk memperoleh pendidikan tidak bisa dipungkiri merupakan warisan dari tradisi keagamaan Islam yang terpengaruh bias patriarki ketika hukum fiqh dikodifikasikan. Walaupun tradisi itu sendiri tidak selalu didukung oleh Al Qur'an, bagaimanapun telah dan akan terus berpengaruh dalam menentukan kesempatan yang tersedia bagi perempuan. Sehingga fakta minimnya pendidikan bagi perempuan menjadi fenomena lazim di dunia Islam.